Characterizing the interfacial zones of fly ash based alkali activated adhesives to various substrates - Wisniewski, Wolfgang; Ducman, Vilma (Frontiers in Materials, 2022)
Alkali Activated Materials (AAMs) are important potential substitutes for cement in many materials. The AAMs presented here are based on industrial ground granulated blast furnace slag (GGBFS) and fly ash (FA). They are tested for their suitability as adhesives for joining concrete, ceramic tiles, a wood-based geopolymer (WGP) and a high density geopolymer (HDGP). After mixing multiple batches and performing preliminary tests of the resulting shrinkage, bending-, compressive- and pull-of-strengths to standard ceramic tiles, selected mixtures are tested for their open time and applied to bond intended substrates. The interfacial zones (ITZ) of an AAM containing additional KOH and the most comparable KOH-free AAM to concrete, ceramic tiles, WPG and HDGP are subsequently characterized in detail using scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDXS). Both mechanical interlocking and areas of probable chemical bonding are identified.